1998
DOI: 10.1038/2477
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a prostate cancer susceptibility locus on the X chromosome.

Abstract: Over 200,000 new prostate cancer cases are diagnosed in the United States each year, accounting for more than 35% of all cancer cases affecting men, and resulting in 40,000 deaths annually. Attempts to characterize genes predisposing to prostate cancer have been hampered by a high phenocopy rate, the late age of onset of the disease and, in the absence of distinguishing clinical features, the inability to stratify patients into subgroups relative to suspected genetic locus heterogeneity. We previously performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 565 publications
(88 citation statements)
references
References 21 publications
(4 reference statements)
3
85
0
Order By: Relevance
“…This region is also reported to harbor a gene involved in PCa susceptibility (Xu et al, 1998). ZNF185 mRNA expression was detected in several normal human tissues by Northern blot analysis, and was most abundant in the prostate.…”
Section: Introductionmentioning
confidence: 94%
“…This region is also reported to harbor a gene involved in PCa susceptibility (Xu et al, 1998). ZNF185 mRNA expression was detected in several normal human tissues by Northern blot analysis, and was most abundant in the prostate.…”
Section: Introductionmentioning
confidence: 94%
“…Similar findings have been reported in literature (Bubendorf et al, 1999;Cher et al, 1996;Visakorpi et al, 1995a;1995b). The observation that gain of the whole X chromosome was the most recurrent abnormality of this chromosomes suggests that also other genes on chromosome X, possibly the recently identified second cancer susceptibility locus on Xq27-q28 (Xu et al, 1998), might be of importance for the progression of prostate cancer.…”
Section: Amplificationsmentioning
confidence: 99%
“…Six prostate cancer susceptibility loci (HPC1 at 1q24-25 (Smith et al, 1996), PCAP at 1q42-43 (Berthon et al, 1998), HPCX at Xq27-28 (Xu et al, 1998), CAPB at 1p36 (Gibbs et al, 1999), HPC20 at 20q13 (Berry et al, 2000) and HPC2 at 17p12 (Tavtigian et al, 2001)) and two candidate susceptibility genes (HPC2/ELAC2 at 17q (Tavtigian et al, 2001) and RNASEL at 1q24-25 ) have been reported.…”
mentioning
confidence: 99%